Hypophylax, Hypocnemoides and Myrmoderus (Aves, Formicariidae) as army ant followers - Willis, Edwin O. [UNESP] (Sociedade Brasileira de Zoologia, 1983)
Hylophylax naevia of moderately dense forest undergrowth and H. punctulata of open swamp undergrowth tend to sally for arthropods in low foliage rather than sally to the ground among large ant-following antbirds. They and related Hypocnemoides melanopogon of swamp understory edges are also limited by their microhabitat niches in following ants. Myrmoderus ferrugineus and M. loricatus, ground-walking small antbirds seemingly derived from Hylophylax, follow ants infrequently, probably because ants, large ant-following birds, and predators would attack them if they did so.